060 The acute haemodynamic effects of intravenous sodium nitrite in healthy volunteers during normoxia and hypoxia. (22nd September 2015) - Arif, S; Maher, AR; Ormerod, J O M; Mohan, S; Madhani, M; Frenneaux, M P
Abstract : Background: Nitric oxide (NO) is an important endogenous paracrine vasodilator. The nitrite anion represents an alternate humoural source of NO under hypoxic and/or acidotic conditions. During hypoxia and ischaemia, the usual production of NO by NO synthase enzymes, is markedly reduced. Recently it has emerged that nitrite serves as a biological reservoir for NO under hypoxic conditions. Animal studies have shown that exogenous treatment with nitrite has important hypoxia-specific vasodilator and cytoprotective effects. Our group demonstrated that when administered intra-arterially under normoxic conditions, nitrite substantially vasodilated the venous capacitance bed, but only modestly dilated resistance human forearm vessels. In contrast during hypoxia, potent vasodilation was also observed in resistance vessels. Therefore, in this study we assessed the effects of nitrite on cardiac and peripheral haemodynamics in humans. We hypothesised that an intravenous infusion of sodium nitrite would cause a significant reduction in blood pressure during hypoxia compared to normoxia. Methods: Thirty-three healthy subjects (mean age 32±10 years) were recruited. An intravenous infusion of sodium nitrite was administered at incremental doses (3, 8, 30 and 60 μmol/min) during normoxic or hypoxic conditions in random order. Hypoxia was administered by asking subjects to inspire 12% oxygen via a facemask until oxygen saturations of 83–88% were achieved. Haemodynamic measurements were determined non-invasively through the use of impedance cardiography (Taskforce ® ). Aplanation tonometry (SphygmoCor) was used to delineate central (aortic) blood pressure (CBP). Results: To allow for the time-dependent effect of hypoxia all measurements in this group were placebo-corrected. During hypoxia, systolic blood pressure (SBP) fell by a mean of 11 mmHg (123±19 mmHg to 112±15 mmHg, p≤0.05) from baseline during peak nitrite dose. There was a non-significant reduction in SBP during normoxia of 6 mmHg (120±13 mmHg to 114±22 mmHg, p=NS). No significant changes were observed in stroke volume or cardiac output in either group. In the hypoxia group, total peripheral resistance mirrored changes in SBP. CBP fell in both groups (9 vs13 mmHg, normoxia vs hypoxia, p=NS) from baseline. No significant changes were observed in parameters between the normoxia and hypoxia group. Conclusion: An acute intravenous infusion of nitrite was safe and well tolerated in healthy volunteers. A significant decrease in blood pressure was observed during hypoxia, but not during normoxia, thus supporting the role of nitrite as a hypoxia-specific vasodilator.